Emerging Novel Anti HIV biomolecules from marine Algae: An overview - Sureshbabu Nagarajan, Manikannan Mathaiyan (Journal of Applied Pharmaceutical Science, 2015)
Over the past 3 decades, despite enormous scientific advancements and developments in the field of vaccine development and drugs, HIV-1 is still posing a major challenge to human health. While development of vaccines is still clearly many years ahead, administration of FDA approved drugs leads to severe side effects and toxicity. Marine algae due to its biodiversity has been a rich source of biologically active compounds with varying degree of actions such as anti-viral, anti-cancer, anti-amyloid, anti-inflammatory and anti-oxidant properties. The primary and secondary metabolites obtained from the marine algae have shown potent anti-viral activities in vitro and in animal model. This review focus on the bioactive compounds from marine algae that have been recently identified and studied.
Keywords: Anti-viral compounds,Marine Algae,Sulfated polysaccharides,Vaccines,Anti retroviral drugs.